2020
DOI: 10.5194/wes-5-245-2020
|View full text |Cite
|
Sign up to set email alerts
|

Periodic dynamic induction control of wind farms: proving the potential in simulations and wind tunnel experiments

Abstract: Abstract. As wind turbines in a wind farm interact with each other, a control problem arises that has been extensively studied in the literature: how can we optimize the power production of a wind farm as a whole? A traditional approach to this problem is called induction control, in which the power capture of an upstream turbine is lowered for the benefit of downstream machines. In recent simulation studies, an alternative approach, where the induction factor is varied over time, has shown promising results. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 21 publications
(43 reference statements)
1
32
2
Order By: Relevance
“…Wind farm control is widely recognized as one of the main solutions to mitigate wake effects (Gebraad et al, 2016;Fleming et al, 2016;Vali et al, 2017;Raach et al, 2018;Fleming et al, 2019). In wind farm control, the turbines in a wind farm operate in a coordinated, collaborative fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Wind farm control is widely recognized as one of the main solutions to mitigate wake effects (Gebraad et al, 2016;Fleming et al, 2016;Vali et al, 2017;Raach et al, 2018;Fleming et al, 2019). In wind farm control, the turbines in a wind farm operate in a coordinated, collaborative fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Following actuator disk theory (Burton et al, 2011), P p equals 3. However, simulations have shown for the NREL 5 MW turbine that P p equals 1.88 (Gebraad et al, 2016a). Recent work has shown that P p differs for freestream and waked turbines (Liew et al, 2020).…”
Section: Lifting Line Wake Modelmentioning
confidence: 99%
“…with a p, i = 1 2 1 − 1 − C T, i . The parameter η is tuned to match the manufacturer-provided, yaw-aligned C P look-up table (Gebraad et al, 2016a). The applicability of this model is limited to Region II of the wind turbine power curve which is typically between 4 and 15 m s −1 .…”
Section: Lifting Line Wake Modelmentioning
confidence: 99%
See 2 more Smart Citations